The Influence of Managerial and Family Ownership on Corporate Social Responsibility: Evidence from Indonesia - Rhala Fitria Inayah; Fauzan Fuadi (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study aims to examine the impact of managerial ownership and family ownership on Corporate Social Responsibility (CSR) disclosure in companies listed in the LQ45 Index on the Indonesia Stock Exchange during the 2019-2022 period. This study employs a quantitative approach and uses secondary data from annual financial and sustainability reports. Data analysis was carried out using multiple linear regression analysis, and testing was carried out using STATA 14.0 statistical tools to test the effect of managerial ownership and family ownership on corporate social responsibility (CSR) disclosure. The results of this study show that managerial ownership has a negative effect on CSR disclosure, which suggests that higher managerial ownership correlates with less transparency in CSR reporting. In contrast, the results of this study show that family ownership does not significantly affect CSR disclosure, which indicates that family-controlled companies do not necessarily exhibit better CSR reporting practices. This study provides practical implications for policymakers and corporate stakeholders by emphasising the need for a regulatory framework that encourages transparent and fair CSR disclosure.